12x+11=14x+1

Simple and best practice solution for 12x+11=14x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x+11=14x+1 equation:


Simplifying
12x + 11 = 14x + 1

Reorder the terms:
11 + 12x = 14x + 1

Reorder the terms:
11 + 12x = 1 + 14x

Solving
11 + 12x = 1 + 14x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-14x' to each side of the equation.
11 + 12x + -14x = 1 + 14x + -14x

Combine like terms: 12x + -14x = -2x
11 + -2x = 1 + 14x + -14x

Combine like terms: 14x + -14x = 0
11 + -2x = 1 + 0
11 + -2x = 1

Add '-11' to each side of the equation.
11 + -11 + -2x = 1 + -11

Combine like terms: 11 + -11 = 0
0 + -2x = 1 + -11
-2x = 1 + -11

Combine like terms: 1 + -11 = -10
-2x = -10

Divide each side by '-2'.
x = 5

Simplifying
x = 5

See similar equations:

| 17t+15=11t+51 | | 6y-15=-5y+18 | | (4n-1)(2n+4)= | | 4y+4=3y-6 | | 8x+3=13+3x | | (5a^2x+3ax^2-5x)+(2a^2x-5ax^2+7x)= | | 12x-10=62 | | -5(X+3)2(x-1)=-14 | | 8(2)+5= | | -9w-19=4w-6 | | -9-(4)(2)(x)=3249 | | 8x^2-21x+10=0 | | 8x^2-1x-9=0 | | 10w+16=10w+16 | | 3.2q-4.1-4.6q=-2.4q-3.2 | | 1+p+5+p=-2 | | 6r(2r-1)= | | 5x+24=12x+60 | | 6m+10=25-m | | 5x+11=12x+60 | | (5x^2-x-7)+(2x^2+3x+4)= | | 20e+50f=8(40) | | 22x-26x=10-14 | | -10-8x=-110+6 | | 3x-5y-4y+9x+2= | | 2xa-11=-5 | | 5x=48+2x | | (5x+3o)+9o= | | -3(4)+-2=x | | -(x-1)-4(x-3)=58 | | -0.2(-15x-10)=10 | | -7(4)+15=x |

Equations solver categories